Controllability and Ulam–Hyers stability analysis of conformable fractional differential systems with time delays and impulsive effects - Zhang, Luchao; Liu, Xiping; Jia, Mei; Yu, Zhensheng; He, Changxiang (Nonlinear Analysis: Modelling and Control, 2026)
We investigate the controllability and Ulam–Hyers stability of a class of conformable fractional differential systems with time delays and impulsive effects. Specifically, we analyze the movement rules before and after the impulse, utilizing both the Banach and Schauder fixed point theorem to derive controllability. Furthermore, we employ nonlinear functional analysis methods to study Ulam–Hyers stability. To demonstrate the applicability and feasibility of our main conclusions, an illustrative example is provided.